Performance lies my professor told me the case for teaching Software Performance Engineering to undergraduates. - Dugan, Robert F.
In this paper we report a survey examining the approach to performance and software engineering in courses at highly ranked computer science schools in the United States. An analysis of the survey shows serious shortcomings including inadequate or missing definitions of performance, reactive "fix it later" mentality, vague performance requirements, and a general lack of awareness of the practices developed by the Software Performance Engineering (SPE) community. The survey is followed by guidelines for teaching SPE to undergraduates based on a semester long course we have developed. It is our plan to incorporate these guidelines into the curriculum of our senior capstone software engineering course.
Keywords: Information systems; Information systems applications; Education; Performance; Software engineering